NILAI RELIGIUS DAN NILAI MORAL PADA CERITA RAKYAT BULUSAN DI KABUPATEN KUDUS (International Forum of Researchers and Lecturers, 2023)
The problem that often occurs is that some people do not understand the existence of exemplary values contained in the folklore of Bulusan. This study aims to describe exemplary values in the Bulusan folklore, namely the religious values and moral values contained in the Bulusan folklore. The method used in this study is qualitative with a qualitative descriptive analysis method and the data sources come from community leaders, village heads, local residents, and practitioners who are experts in knowing and understanding Bulusan folklore. In this study using data collection techniques by way of observation, interviews, recording, recording, photographing, and transcription. In this study, the validity of the data was used, namely triangulation of sources, time, and techniques. Based on the analysis of the data obtained in the Bulusan Folklore, there are also character values that can serve as guidelines and examples for the whole community, especially young people for the next generation. The origins of the Bulusan folklore have several religious values and moral values contained in it. The content of religious values in Bulusan folklore includes obedience, belief, and practice. The moral values contained in the Bulusan folklore are the values of mutual cooperation, obedience, and politeness.